Clinical 3-tesla FLAIR* MRI improves diagnostic accuracy in multiple sclerosis. (October 2016) - George, Ilena C; Sati, Pascal; Absinta, Martina; Cortese, Irene CM; Sweeney, Elizabeth M; Shea, Colin D; Reich, Daniel S
Objective: To evaluate clinical fluid-attenuated inversion recovery (FLAIR)* 3T magnetic resonance imaging (MRI), which is sensitive to perivenular inflammatory demyelinating lesions, in diagnosing multiple sclerosis (MS). Background: Central veins may be a distinguishing feature of MS lesions. FLAIR*, a combined contrast derived from clinical MRI scans, has not been studied as a clinical tool for diagnosing MS. Methods: Two experienced MS neurologists evaluated 87 scan pairs (T2 -FLAIR/FLAIR*), separately and side-by-side, from 68 MS cases, 8 healthy volunteers, and 11 individuals with other neurological diseases. Raters judged cases based on experience, published criteria, and a visual assessment of the "40% rule, " whereby MS is favored if >40% of lesions demonstrate a central vein. Diagnostic accuracy was determined with area under the receiver operating characteristic curve (AUC), and inter-rater reliability was assessed with Cohen's kappa (κ). Results: Diagnostic accuracy was high: rater 1, AUC 0.94 (95% confidence interval: 0.89, 0.97) for T2 -FLAIR, 0.95 (0.92, 0.98) for FLAIR*; rater 2, 0.94 (0.90, 0.98) and 0.90 (0.85, 0.95). AUC improved when images were considered together: rater 1, 0.99 (0.98, 1.00); rater 2, 0.98 (0.96, 0.99). Inter-rater agreement was substantial for T2 -FLAIR (κ = 0.68) and FLAIR* (κ = 0.74), despite low agreement on the 40% rule (κ = 0.47) (p ≪ 0 . 001 in all cases). Conclusions: Joint clinical evaluation of T2 -FLAIR and FLAIR* images modestly improves diagnostic accuracy for MS and does not require counting lesions with central veins.